My Brother as "Problem": Neoliberal Governmentality and Interventions for Black Young Men and Boys. (January 2016) - Dumas, Michael J.
In this article, the author argues that the Obama Administration's My Brother's Keeper (MBK) initiative serves as an exemplar of neoliberal governmentality, in which Black young men and boys are constructed as essentially damaged, as problems in need of a technocratic public–private solution. More than simply an ideological imposition from above or outside—from policy makers, state bureaucrats, or market actors—MBK signals the neoliberal turn in Black politics, in which technical, entrepreneurial interventions replace political organization as the imagined solution to the social and economic inequities experienced in Black life. The author highlights three discursive "moments" that capture the work neoliberal governmentality does in and through MBK, and offers discussion of what it might mean to pursue a more critical engagement with MBK and other neoliberal initiatives intended to address racial inequities in education and society.